PENGARUH PEMBELAJARAN DARING MELALUI WHATSHAPP GROUP (WAG) DENGAN BERBANTU MEDIA VIDEO PEMBELAJARAN TERHADAP PEMAHAMAN KONSEP IPA PADA PESERTA DIDIK MI YAA BUNAYYA - Ika Putra Viratama; Prihaten Maskhuliah (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2020)
Abstract. Research has been conducted on the effect of instructional video media on understanding the concept of science. The purpose of this study was: to determine the effect of E-Learning with the help of instructional video media on understanding the concept of science in MI Yaa Bunayya students. This type of research is using quantitative methods. The quantitative method is called the traditional method, because this method has been used for a long time so that it has become a traditional method for research. This method is called the positivistic method because it is based on the philosophy of positivism. This method is a scientific / scientific method because it meets scientific principles, namely concrete / impiric, objective, measurable, rational, and systematic. This research test instrument technique used a test made by researchers in the form of multiple choices (Multiple Choise Item Test) consisting of 15 items with 4 options. The test questions relate to the thinking level of Bloom's taxonomic domain. For data analysis used simple regression analysis test. Based on the output of SPSS 18, it is known that the significance value (Sig) of 0.001 is smaller than the probability of 0.005, so it can be concluded that Ho is rejected and Ha is accepted, which means that there is an effect of E-Learning with the help of instructional video media on understanding the concept of science in MI students. Bunayya.